High density of shear bands in the Vitreloy bulk metallic glass subjected to high-pressure torsion. Issue 1 (December 2020) - Astanin, Vasily; Gunderov, Dmitry; Qiang Ren, Zhi; Valiev, Ruslan; Wang, Jing Tao
Abstract: Plastic deformation by high-pressure torsion allows one to achieve high strains of bulk metallic glasses without their failure. It is shown that inclusions of the primary crystalline phase in the Vit105 alloy provoke the formation of cracks, and shear bands themselves have a complex composite structure and are prone to branching and merging during the development of deformation. The density of the bands reaches 1.76 μm −1, with a distance between them 80-120 μm.